Impact of Hotel Service Quality Dimensions on Hotel Brand Image and Guest Repeat Patronage - Singh, Ramjit (2023)
The present research aims to assess the structural relationship between service quality and guest repeat patronage in the hospitality industry, examining examines the service quality, hotel brand image, and guest repeat patronage.  The research design is exploratory cum descriptive in nature. The primary data were collected in June-August 2019 and 400 were considered valid responses for analysis. SPSS 21 was used for data treatment and descriptive analysis, exploratory factor analysis, t-test, ANOVA, and structural equation modelling (SEM), and a multilateral technique was provided. The factors of service quality like tangibility and empathy have shown the maximum variance explained. It indicates that the guests have felt these two factors are more important in enhancing their satisfaction level. Overall, better service quality in hotels enables them to achieve higher guest satisfaction and retention. The more and better the hotel's service diversity, the more positive the brand image developed in guests' minds, influencing their repeat patronage. The present research contributes to the theory of the vital concepts of service quality, brand image, and guest repeat patronage. It clarifies the positive relationship between service quality, brand image, and guest repeat patronage to improve the hotel's service quality and brand image.